Calcium signaling : from physiology to diseases - Rajagopal, Senthilkumar; Ponnusamy, Murugavel (Springer, 2017)
This book focuses on disorders of calcium channels and the use of drugs to treat calcium-related disorders and their associated toxicities. In particular, it discusses the role of various natural products and their attributes in preventing problems associated with calcium imbalances. In addition, the book analyzes trends in the processing of natural products using nanotechnology and their implications in calcium-related disorders. Lastly, it explores some of the most promising aspects of research into calcium signalling disorders - which is especially important, given the wide variety of cellular processes that are controlled by calcium ions - and provides a trustworthy source of up-to-date information in this area of research.
Keywords: Calcium ions.; Cellular signal transduction.; elektronické knihy; electronic books